Ultrasonic color Doppler imaging to assess the efficacy of orbital decompression in Graves’ ophthalmopathy - A.A. Kalandari; A.G. Nosova; N.Yu. Kutrovskaya; O.V. Levchenko (РМЖ "Клиническая офтальмология")
A.A. Kalandari, A.G. Nosova, N.Yu. Kutrovskaya, O.V. Levchenko Moscow State University of Medicine and Dentistry named after A.I. Evdokimov, Moscow, Russian Federation Orbital soft tissue ultrasound is particularly important for specialists providing care for Graves’ ophthalmopathy (GO). In addition to echo signs of non-inflammatory edema and/or proliferation of retrobulabar fat, extraocular muscle thickness, their density, and contractility, changes in orbital blood flow should be considered as well. Multiple previous studies demonstrate reduced blood flow in the superior ophthalmic vein. However, recent studies poorly address this issue, therefore, these publications are vital to investigate the problem. Ultrasonic color Doppler imaging evaluates hemodynamic changes in the orbital blood flow in GO. Changes in linear blood flow velocity in the superior ophthalmic vein are an additional diagnostic criterion for the severity of autoimmune disorder in these patients. Abnormalities of venous blood flow promote non-inflammatory edema of retrobulbar fat, proptosis, and orbital compression. However, linear blood flow velocity in the oph thalmic artery, central retinal artery, and posterior ciliary arteries as well as arterial resistive index should be also considered to predict disease course and to sel ect treatment strategy. Evaluation of hemodynamic changes and their severity can specify the terms and surgical strategy for GO. Being safe and non-invasive tool, ultrasonic colour Doppler imaging can be applied postoperatively. Improved superior ophthalmic vein blood flow fr om orbital soft tissues and reduced resistive index of ophthalmic artery are potential criteria for GO surgery efficacy. Keywords: Graves’ ophthalmopathy, hemodynamic changes in orbital vessels, superior ophthalmic vein, ophthalmic artery, color-flow duplex scanning, orbital decompression. For citation: Kalandari A.A., Nosova A.G., Kutrovskaya N.Yu., Levchenko O.V. Ultrasonic color Doppler imaging to assess the efficacy of orbital decompression in Graves’ ophthalmopathy. Russian Journal of Clinical Ophthalmology. 2019;19(3):150–153.